Multimodality Treatment of Pulmonary Sarcomatoid Carcinoma: A Review of Current State of Art. (25th March 2022) - Zhang, Lin; Lin, Weihao; Yang, Zhenlin; Li, Renda; Gao, Yibo; He, Jie
Abstract : Pulmonary sarcomatoid carcinoma (PSC) is an unconventional non-small-cell lung cancer (NSCLC) that is currently managed under guidelines used for conventional NSCLC and has poor survival. Surgery is the optimal choice for resectable PSC, and the prevalence of mutations in this type of tumor laid the foundation for novel systemic therapies such as targeted therapy and immunotherapy. PSC is resistant to chemotherapy and radiotherapy, and the effects of the 2 therapies are controversial. Targeted therapies have been reported to confer survival benefits, and savolitinib, an oral selective MET tyrosine-kinase inhibitor, has been approved in metastatic patients with MET exon 14 skipping mutations. Expression and positive rate of programmed death ligand 1 in PSC are high; our previous research has also revealed a high mutational burden and a T-cell-inflamed microenvironment of PSC. Correspondingly, immune checkpoint inhibitors have shown preliminary antitumor effects (overall response rates of 40.5% (15/37) and 31.6% (6/19) in two retrospective studies, respectively) in PSC patients. In summary, patients should receive operations at an early stage and multimodality treatments are needed to maximize the benefits of patients with advanced disease.